Ionic interdiffusion as interaction mechanism between Al and Si3N4. Issue 8 (25th February 2019) - Adabifiroozjaei, Esmaeil; Koshy, Pramod; Emadi, Fahimeh; Mofarah, Sajjad S.; Ma, Hongyang; Rastkerdar, Ebad; Lim, Sean; Webster, Richard F.; Mitchell, David R.G.; Sorrell, Charles C.
Abstract: Al‐Si3 N4 couples were heat‐treated at 850‐1150°C for 250 hours. The thickness of the interacted area was measured by scanning electron microscopy (SEM) and scanning/transmission electron microscopy (TEM/STEM). The interaction rate increases exponentially with inverse temperature, with an activation energy of 194.23 kJ/mol and diffusion pre‐coefficient of 5 × 10 −9 m 2 /s, indicating that the interaction is diffusion‐dependent. As the results showed, the interfacial area is comprised of Al alloy channels, Si precipitates, and AlN grains. Al‐Si transfer through the solid solution (Si3‐x Alx N4‐y ) at the interface of Al alloy and β‐Si3 N4 grains controls the kinetic of the interaction. When concentration of Al in solid solution exceeds a certain amount, it undergoes a topotactic phase transformation to form Al1‐x Six N1+y ( viz ., AlN). Next, the Al1‐x Six N1+y grains detach from the β‐Si3 N4 grains and subsequently new Al‐Si3 N4 interfaces are established. These interfaces repeat the interaction process, continuing until all the reactant is depleted. Thus, the interaction kinetics consist of a sequence of associated parabolic stages, precluding the observation of parabolic kinetics.